Rohdea brachyanthera (Asparagaceae), a new species from Guangdong, southern China - Feng, Hui Zhe; Tong, Yi; Wu, Lei; Gong, Yue Ning; Liao, Wen Bo (Phytotaxa, 2023)
Rohdea brachyanthera, a new species from Nanling National Reserve of northern Guangdong, China, is described and illustrated. It is most similar to R. fargesii var. tsinlingensis in the perianth tube bearing an appendage at apex and the stamens are attached to it, but differs in the smooth inner surface of the perianth and stamens; the presence of six rib-like protrusions on the internal surface of the perianth tube; a ring-shaped, succulent appendage that is outwardly swollen and smooth on the surface and dilated triangular filaments that are united with the appendages at the base. Information on the habitat and phenology as well as notes on the taxonomic relationships with other congeners is also provided.